EFEKTIVITAS PEMBELAJARAN KITAB TA’LIM MUTA’ALLIM DALAM MEMBENTUK SIKAP BELAJAR SANTRI DI PESANTREN AL-KAHFI KOTA BEKASI - Rif'ah, Rif'ah; Shofiyat, Ali Ilham; Oktapiani, Marliza (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
There are several factors that can influence students learning success. One factor that often becomes an issue in studdents learning success is a low level of positive attitudes and study habits. Examples include frequently procrastinating when working on assignments given by the teacher, not paying attention to or respecting teachers when they are explaining the lesson, leaving the classroom or skipping classes during lesson time, or disturbing classmates during class hours. In writing this thesis, the author uses a qualitative approach with a case study method. As per the procedures for obtaining qualitative data, the research data is collected through several techniques, such as interviews, observations, and documentation. The research results indicate that the implementation of learning the Ta'lim Muta'allim book at Al-Kahfi Islamic Boarding School uses the bandongan and sorogan methods. Learning the Ta'lim Muta'allim book at Al-Kahfi Islamic Boarding School contributes to shaping better learning attitudes among the students. The changes in learning attitudes experienced by the students include their attitudes towards themselves, their attitudes towards scholars/teachers, their attitudes towards friends, and their attitudes towards knowledge/books. The students develop good study habits such as reviewing lessons, praying before studying, respecting fellow students, and honoring their teachers.